An ARDL approach in studying the impact of ASF and selected factors on the Philippine pork market retail price - Ebal, Lara Paul A. (Journal of Economics, Management & Agricultural Development, 2021)
This study aimed to explore the impact of the farmgate price of hogs, the volume of hog production, the volume of imported pork, the market retail price per kilo of dressed chicken, the quantity of pork consumed by the population, the GDP per capita, and African Swine Fever (ASF) on the pork market retail price in the Philippines. The Autoregressive Distributed Lag (ARDL) approach was implemented to model the pork price using quarterly data from 2000 to 2020. The long-run model showed that farmgate price, hog production, and imported pork during the presence of ASF could affect pork price. Moreover, the short-run model confirmed that the ASF outbreak had an impact on pork price, and during the presence of ASF, farmgate price of pork decreased while the price of imported pork increased. Farmgate price, hog production, and chicken price also had an impact on pork price.